The influence of the cast iron structure upon the hardness of brake shoes meant for the rolling sock. Issue 1 (May 2015) - Socalici, A; Pascu, L; Popa, E; Hepuţ, T
Abstract: An important characteristic with a high impact upon the exploitation durability of the brake shoes is hardness. The paper introduces the influence of the phosphorous cast iron structure upon the hardness of the brake shoes meant for the tractive and trailing rolling stock. The results presented show the variation of hardness on the surface and the cross section of the braking shoe